Techno-economic Evaluation of Bed Seeding Technique in Wheat Crop - Kumar, Vivek; Sharma, D N; Sardana, P K (Journal of Agricultural Engineering, 2002)
Comparative evaluation of raised bed system for seeding of wheat crop over existing method was undertaken to optimize furrow and bed dimensions with respect to crop parameters. Bed width of 45 cm with 30 x 20 cm size of furrow was found to be optimum having adequate soil moisture availability and its more uniform distribution in sandy loam soil. Seed germination, crop stand, yield and yield attributes were higher in 45 cm bed width having 3 x 15 cm row spacing and 6 cm depth of sowing. The performance evaluation of two-row tractor drawn bed planter in comparison with flat sowing was carried out on the basis of optimum bed and furrow parameters determined above. There was no significant effect of method of sowing on seed germination and crop stand. But, yield attributes, namely, number of ears/m length and 1000 grain weight were significantly higher in crop sown with bed planter. Slightly higher grain and straw yields were recorded in flat system (36.42 q/ha and 63.82 q/ha) as compared to bed planter (34.79 q/ha and 58.40 q/ha). In bed planting there was considerable reduction in weed population before and after chemical control. There was 41.5 % saving in irrigation water and 25.41 % reduction in cost of operation. The energy required per quintal of grain produced was also significantly lower in bed planter (33.2 %) over flat ’method due to saving in labor used for making basins in flat method and irrigation through furrows.